Solidaritas dan Modal Sosial Pedagang Pasar Legi Surakarta Menghadapi Tantangan Pasar Modern - Ghoni Arifin; Yosafat Hermawan Trinugraha; Nurhadi Nurhadi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2021)
This paper aims to analyze how the traders association of Pasar Legis (IKKAPAGI) becoming social capital for traders into face development of modern markets in Banjarsari Subdistrict, Surakarta City. This study uses qualitative research methods with case study approaches. Data collection techniques are interviews, observation, and document collection. The data analysis was done in three stages, namely: data reduction, data presentation, and conclusion. The results of this study show that social obligations and expectations, information flows, values, ​​and norms are social capital used by traders to maintain the existence of traditional markets in the midst of many modern markets. IKKAPAGI is a mean for improving the quality of the Pasar Legi and ais s a source of social capital for traders, I t serves as a forum for organizing and accommodating the aspirations of traders, sharing information, and also acting as a facilitator in expanding the network of cooperation to maintain business in the midst of many modern markets.